Formulation of Customary Criminal Sanctions From a Human Rights Perspective - Erni Dwita Silambi; Rosnida Rosnida; Enni Eka kusumawati (Jurnal Hukum Volkgeist, 2022)
The provision of customary criminal sanctions varies according to the customs and norms that apply in an area and this research takes a case study in Merauke Papua. This research focuses on the provision of customary sanctions for perpetrators which will be viewed from the point of view of human rights. This study aims to see and analyze the criminal sanctions given to the perpetrators and whether these sanctions do not conflict with the human rights that apply in Indonesia. The type of research used in this research is a combination of normative legal research and empirical legal research where normative research will look at legislation related to human rights and also provisions regarding customary sanctions while empirically will look for direct data in the field then data analyzed using qualitative methods will then be presented descriptively. The results of this study are that customary law does not recognize the division between criminal law and civil law but the sanctions given to both criminal cases and civil disputes are the same, namely tubers, coconuts, bananas, wati (a typical Papuan plant), pigs, giving sister and the death penalty, pay with the land that has been determined.